Collaborative Governance in the Development of Marine Tourism in Taka Bonerate National Park, Selayar Islands Regency - Putra, Muhammad Amril Pratama; Anriandi, Anriandi (Universitas Muhammadiyah Makassar, 2025)
This qualitative case study aims to explore the dynamics of collaboration in the management of Taka Bonerate tourism comprehensively and contextually. The study reveals that while collaboration processes have been implemented relatively well, involvement of community groups remains institutionally weak, communication is insufficient, trust between parties is lacking, and commitment is not yet strong despite adherence to official regulations. Collaborative actions, especially facilitation through training and socialization, are limited, with infrequent meetings among stakeholders hindering progress. Nevertheless, the collaboration has positively impacted the community by increasing tourism awareness and creating income opportunities. These findings highlight the need to strengthen communication, trust, and commitment, as well as to enhance capacity-building efforts to improve collaborative tourism management in Taka Bonerate